Endurance Exercise Training reduces Blood Pressure according to the Wilder’s Principle - Mora-Rodriguez, Ricardo; Ortega, Juan Fernando; Morales-Palomo, Felix; Ramirez-Jimenez, Miguel; Moreno-Cabañas, Alfonso; Alvarez-Jimenez, Laura (International Journal of Sports Medicine, 2021)
The effect of antihypertensive medicine (AHM) is larger the higher the pre-treatment blood pressure level. It is unknown whether this Wilder’s principle, also applies for the exercise-training blood pressure (BP) lowering effect. One hundred seventy-eight (n=178) middle-aged individuals (55±8 y) with metabolic syndrome (MetS), underwent high intensity interval training (3 days·week–1) for 16 weeks. Participants were divided into medicated (Med; n=103) or not medicated (No Med; n=75) with AHM. Office BP was evaluated before and after the exercise-training. Correlations and stepwise regression analysis were used to determine which variable better predicted the reductions in systolic BP (SBP) with training. After training, participants with hypertension lowered SBP by a similar magnitude regardless of if they were in the Med (–15 mmHg, 95% CI–12,–19; P<0.001) or No Med group (–13 mmHg, 95% CI–9,–16; P<0.001). However, SBP did not decrease among normotensive groups (P=0.847 for Med and P=0.937 for No Med). Pre-treatment SBP levels was the best predictor of exercise-training lowering effect (r=–0.650; β=–0.642; P<0.001). For each 10 mmHg higher pre-training SBP there were a 5 mmHg deeper SBP reduction (Wilder principle). Furthermore, AHM does not interfere with exercise-training BP-lowering effect.
Keywords: aerobic interval training; cardiovascular diseases; hypertension; metabolic syndrome; office blood pressure; Wilder’s principle